СЛОВО О ИСААКУ У ХИЛАНДАРСКОЈ ПАЛЕЈИ СА ТУМАЧЕЊЕМ (Prilozi za književnost, jezik, istoriju i folklor, 2024)
THE TALE OF ISAAC IN THE CHILANDAR PALEIA WITHINTERPRETATIONThis paper deals with the apocryphal The Tale of Isaac in Serbian translation and the first copy of the Paleia with interpretation. The Serbian translation was done at the Chilandar Monastery, using the Russian version, in the course of the year 1633, or possibly the year before, by an unknown Chilandar monk. The first copy of this translation was written out by the Chilandar priest Damascene in the year stated above, relying on the translation manuscript written that same year. The manuscript of the Serbian translation is preserved at the Cetinje Monastery (marked no 84), and Damascene’s copy is kept at Chilandar, marked no 188. Comparing the translation with the Russian version, Damascene observed mistakes in the translation and corrected them in his copy. Even though there was a Russian copy of the Paleia with interpretation at Chilandar, donated from the city of Kovel, in all likelihood it was not used as the basis for translation by the Serbian translator, who relied on some other unknown Russian copy. The appendix contains the edited text of The Tale of Isaac according to Damascene’s copy.